GPR84 regulates pulmonary inflammation by modulating neutrophil functions - Wang Si-wei; Zhang Qing; Lu Dan; Fang You-chen; Yan Xiao-ci; Chen Jing; Xia Zhi-kan; Yuan Qian-ting; Chen Lin-hai; Zhang Yang-ming; Nan Fa-jun; Xie Xin (Acta Pharmacologica Sinica; Vol 44, No 8 (August 2023): Acta Pharmacologica Sinica, 2023)
Acute lung injury (ALI) is an acute, progressive hypoxic respiratory failure that could develop into acute respiratory distress syndrome (ARDS) with very high mortality rate. ALI is believed to be caused by uncontrolled inflammation, and multiple types of immune cells, especially neutrophils, are critically involved in the development of ALI. The treatment for ALI/ARDS is very limited, a better understanding of the pathogenesis and new therapies are urgently needed. Here we discover that GPR84, a medium chain fatty acid receptor, plays critical roles in ALI development by regulating neutrophil functions. GPR84 is highly upregulated in the cells isolated from the bronchoalveolar lavage fluid of LPS-induced ALI mice. GPR84 deficiency or blockage significantly ameliorated ALI mice lung inflammation by reducing neutrophils infiltration and oxidative stress. Further studies reveal that activation of GPR84 strongly induced reactive oxygen species production from neutrophils by stimulating Lyn, AKT and ERK1/2 activation and the assembly of the NADPH oxidase. These results reveal an important role of GPR84 in neutrophil functions and lung inflammation and strongly suggest that GPR84 is a potential drug target for ALI.